PENGALAMAN KOMUNIKASI PERSUASIF PEDAGANG PASAR TRADISIONAL (Studi Fenomenologi Terhadap Pedagang Pasar Anyar Kota Tangerang) - Firda Tita Umami (2021)
Starting from a unique event when visiting one of the traditional markets in Tangerang City, the researcher saw and felt the uniqueness and difference in the persuasive communication process carried out by traditional market traders with what modern market traders did. Traditional market traders do not try to explain the product in detail or formally as is done by traders in malls, but they seem more relaxed and give lots of jokes to buyers in the buying and selling process that occurs. The event that was witnessed by researchers when visiting the traditional market raised the researchers' curiosity about how to experience persuasive communication by traditional market traders to buyers. The persuasive communication experience of market traders was researched using phenomenological methods and data collection through in-depth interviews with traders at Pasar Anyar Tangerang. Phenomenology is chosen to know and deepen the meaning, experience, and motives in the phenomena that occur. Some of the research questions posed are (1) What is the meaning of persuasive communication for traditional market traders, (2) How is the persuasive communication experience of traditional market traders, and (3) What are the motives underlying traditional market traders to make persuasive communication. The results of the findings obtained from the experiences of these workers are in the form of themes of experience, namely: good service, knowing the needs of buyers, not being pushy, not differentiating buyers, being friendly, buying comfort, raising prices, and praising buyers.